2007
DOI: 10.1089/jwh.2006.m078
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Nutrient Intake among Arizona WISEWOMAN Participants

Abstract: Mexican American women had overall lower micronutrient intakes compared with uninsured non-Hispanic white older women; this difference may be attributed to their underreporting intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In the present study, 84 % of the older and 59 % of the younger women had an inadequate Ca intake. In other observations, up to 98 % of older Mexican-American women over 50 years of age did not meet the recommended intake of Ca (56) . Folate intake is of particular concern to childbearing Hispanic women, considering that neural tube defects are more prevalent in Hispanic women (60) , as is an increasing parity rate (61) .…”
Section: Micronutrient and Fibre Intakesmentioning
confidence: 84%
“…In the present study, 84 % of the older and 59 % of the younger women had an inadequate Ca intake. In other observations, up to 98 % of older Mexican-American women over 50 years of age did not meet the recommended intake of Ca (56) . Folate intake is of particular concern to childbearing Hispanic women, considering that neural tube defects are more prevalent in Hispanic women (60) , as is an increasing parity rate (61) .…”
Section: Micronutrient and Fibre Intakesmentioning
confidence: 84%
“…Neushouser et al [27] found that highly acculturated Mexican-Americans had slighter higher, but not statistically significant, scores of fat intake compared to their low acculturated counterparts. Gregory-Mercado et al [49] reported no significant association between acculturation and total fat intake in a sample of Mexican American women. In contrast, a positive association between acculturation and intake of dietary fat was reported in a national sample of youth [50].…”
Section: Discussionmentioning
confidence: 94%
“…Our findings differed from previously reported studies. Five earlier studies have examined acculturation in relation to dietary patterns among older adults (24,31,(37)(38)(39), but only two have focused on older MAs (24,31), and only one of those included information on folate intake and the proportion meeting folate recommendations. None have assessed folate intake from multiple sources.…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded additional persons with (i) unrealistic caloric intake (i.e., <500 or >5000 kcals on either day one or day two (n ¼ 32) (31,32); (ii) persons missing one or more of the acculturation variables (i.e., language spoken or country of origin) (n ¼ 5) and for whom we had no additional data on language or country of origin; and (iii) persons missing information on supplement use (n ¼ 7). These exclusions left a final sample size of 712 older MAs (83.5% of the eligible sample).…”
Section: Analytic Samplementioning
confidence: 99%